Complementarities in the production of child health - Laura Abramovsky; Britta Augsburg; Pamela Jervis; Bansi Malde; Angus Phimister (Institute for Fiscal Studies (IFS), 2019)
This paper estimates flexible child health production functions to investigate whether better water, sanitation and hygiene (WASH) practices make nutrition intake more productive for children aged 6-24 months. Using cohort data, with detailed information on nutrition intake and WASH investments, and a control function approach to account for endogeneity of inputs, we show that better WASH increases the productivity of protein and calories in the formation of child health using as proxies child height and weight. We also uncover heterogeneity in the productivity of these inputs by child gender: nutritional intake is found to be more productive for boys, and WASH investments more productive for girls. Further analysis indicates that this is not driven by differential parental invest-ments by child gender. Although the study sample are children born in the early 1980s they faced similar nutritional and WASH conditions as those faced by children currently living in poor households in low-income settings.
Keywords: I12; I15; O15; O18; Q53; 330; child health; sanitation; nutrition; complementarities; health production function